2014
DOI: 10.1111/apt.12985
|View full text |Cite
|
Sign up to set email alerts
|

The impact of abdominal pain on global measures in patients with chronic idiopathic constipation, before and after treatment with linaclotide: a pooled analysis of two randomised, double‐blind, placebo‐controlled, phase 3 trials

Abstract: BackgroundFew clinical trials in chronic idiopathic constipation (CIC) patients have evaluated abdominal symptom severity and whether CIC patients with abdominal symptoms respond similarly to patients with limited abdominal symptoms.AimsTo examine abdominal symptom severity and relationships between symptoms and global measures at baseline; compare linaclotide's effect on symptoms in subpopulations with more or less abdominal pain; and assess relationships between symptom improvement and global measures in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
22
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 43 publications
4
22
0
1
Order By: Relevance
“…In addition, these results confirm that several other symptoms beside constipation can be prevalent in these patients even though these are not included in the diagnostic criteria. Previous work on the impact of abdominal pain on global measures in patients with chronic idiopathic constipation has shown that the presence of multiple abdominal symptoms positively correlates with ratings of constipation severity . Similar results were observed in our study suggesting that the increased number of additional bowel symptoms could contribute to an increased symptom perception.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In addition, these results confirm that several other symptoms beside constipation can be prevalent in these patients even though these are not included in the diagnostic criteria. Previous work on the impact of abdominal pain on global measures in patients with chronic idiopathic constipation has shown that the presence of multiple abdominal symptoms positively correlates with ratings of constipation severity . Similar results were observed in our study suggesting that the increased number of additional bowel symptoms could contribute to an increased symptom perception.…”
Section: Discussionsupporting
confidence: 90%
“…Previous work on the impact of abdominal pain on global measures in patients with chronic idiopathic constipation has shown that the presence of multiple abdominal symptoms positively correlates with ratings of constipation severity. 15 Similar results were observed in our study suggesting that the increased number of additional bowel symptoms could contribute to an increased symptom perception. The reporting of many other symptoms underlines again that disorders of brain-gut interaction can be part of a continuum and that overlap between these disorders is highly prevalent.…”
Section: Discussionsupporting
confidence: 90%
“…However, a majority of studies in the topic are exclusively available as abstracts presented in congresses. Third, none of the multiple randomised controlled trials published until now that assessed the efficacy of therapy in EoE have considered improvements in QoL as a relevant study outcome, which contrasts with the central importance granted to HRQoL in other chronic digestive diseases . Finally, validated versions of the specific questionnaires to measure HRQoL in other languages to English have not been developed yet (except for a Spanish version of the EoE‐QoL‐A questionnaire), which limits the level of credibility of such instruments, according to Cohen's criteria …”
Section: Discussionmentioning
confidence: 99%
“…Based on the pain cases recorded in pain clinics, many disease-associated studies have been conducted in western countries [15][16][17]. However, reports regarding the epidemiology of detailed patient profiles admitted into pain clinics in China are still rare.…”
Section: Introductionmentioning
confidence: 99%